Psychic distance and cross-border cooperation of SMEs: An empirical study on Saxon and Czech entrepreneurs' interest in cooperation - Cornelia Zanger; Radka Hodicová; Hansjoerg Gaus (Journal for East European Management Studies, 2008)
This paper examines the relationship between the psychic distance of decision makers in SMEs from specific foreign markets and their interest in cooperation with companies from those countries. Based on a review of the literature and a qualitative empirical study among entrepreneurs in the Saxon-Czech border area, the paper identifies the central explanatory variables of psychic distance, thus contributing to a theoretically-based conceptualization of this construct. Previous conceptualizations of psychic distance are extended and specified. This reveals the necessity for a wider inclusion of perceived differences in the political and legal situations, the mind-set as well as the historical development. – – Der vorliegende Beitrag untersucht den Zusammenhang zwischen der psychischen Distanz mittelständischer Unternehmer gegenüber konkreten Auslandsmärkten und ihrer Bereitschaft zur Kooperation mit Unternehmen aus diesen Ländern. Auf Basis des Literaturstandes sowie einer qualitativen empirischen Untersuchung bei Unternehmern im sächsisch-tschechischen Grenzraum werden zentrale Erklärungsvariablen dieses Konstruktes identifiziert, wodurch ein Beitrag zu einer theoretisch fundierten Konzeptualisierung der psychischen Distanz geleistet wird. Die in der Literatur vorzufindenden Konzeptualisierungen der psychischen Distanz werden erweitert und präzisiert. Dabei wird die Notwendigkeit einer stärkeren Einbeziehung von wahrgenommenen Unterschieden in politisch-rechtlichen Bedingungen, Mentalität sowie historischer Entwicklung deutlich.
Keywords: 650; psychic distance; cross - border cooperation; internationalization; SMEs